PEDULI KESEHATAN LANSIA MELALUI CEK KESEHATAN GRATIS DAN BAKTI SOSIAL DI BANJAR KUTRI SINGAPADU TENGAH - Ni Luh Made Intan Kharisma Putri; Ni Made Desy Darmayanti; I Wayan Deni Cahyana; I Gede Agus Surya Dana; I Kadek Mangku Krisnanda Ardana; M. Husin Ashari; I Komang Adi Palgunadi (LP3M Universitas PGRI Mahadewa Indonesia, 2026)
Elderly health is a crucial aspect that needs to be addressed in efforts to improve the quality of life in old age. Elderly people are vulnerable to various health problems due to declining organ function and an increased risk of degenerative diseases. Therefore, activities are needed to support early disease detection and improve the community's social welfare. This community service program was implemented through a free health checkup program and community service program in Banjar Kutri, Singapadu Tengah Village, Sukawati District, Gianyar Regency, Bali. The goal of this activity was to raise awareness among the elderly about the importance of maintaining their health and to help them identify health conditions early. The method used was a descriptive method with a participatory approach that involved the community in every stage of the activity. The results showed that the free health checkup program benefited the elderly by directly assessing their blood pressure, blood sugar, cholesterol, and uric acid levels. Furthermore, the provision of social assistance in the form of basic necessities helped alleviate the community's economic burden. This activity also increased social awareness and community participation in maintaining sustainable health.